Genetic and Environmental Determinants of Beef Quality—A Review - Sakowski, Tomasz; Grodkowski, Grzegorz; Gołebiewski, Marcin; Slósarz, Jan; Kostusiak, Piotr; Solarczyk, Paweł; Puppel, Kamila (Frontiers in Veterinary Science, 2022)
The flavor, quality and composition of beef changes with cattle diet regimen. The quality of meat varies, and that variability is determined by both individuals and environmental factors: age, breed, live weight, fatness degree, plane of nutrition, concentrate: roughage ratio. The strategy for the rearing and feeding of cattle for slaughter should therefore aim at reducing the SFA content and increasing the PUFA and MUFA levels. Many human diseases like atherosclerosis and cardiovascular disease are associated with dietary fat, and their develop process taking a year’s which result can be shorter life and its lower quality. The objective of this review was to describe factors affecting meat quality and fatty acid profile of intramuscular fat of European cattle fed various diets.